Unusual Aspergillus Infection After Dermal Filler Injection. Issue 8 (November 2017) - Shin, Jin Yong; An, Mun-Young; Roh, Si-Gyun; Chang, Suk Choo; Lee, Nae-Ho
Abstract : Abstract: According to a great desire for facial rejuvenation, dermal filler is promising for improving people's appearance without surgery. In a society of plastic surgery, injection of dermal filler is one of the most common procedures for a younger appearance. An increase in patients who have filler injection has been paralleled by a rise in various adverse reactions. Formation of inflammatory or infected nodules is one of the most common long-term complications. Infections can be increased because of improper disinfection of the patient's skin, a poor injection technique, decreased general immunity, and the presence of pathogens. The majority of bacteria are aerobic or facultative aerobic bacteria. This expectation of pathogens is critical for deciding on the antibiotic treatment before confirming the pathogen by microbial culture. The authors experienced unusual culture results in a patient with a chronic inflammatory nodule with abscess formation. The authors report a unique Aspergillus -cultured infection after filler injection.